Environmental disclosure, governance score, and tax avoidance: Evidence from Indonesian energy sector companies - Cahyati, Ari Dewi; Lestari, Tri; Mulyasari, Windu; Idriana, Ina (International Journal of Management and Sustainability, 2023)
The goal of the study was to determine how corporate governance (CG) influences tax avoidance, how environmental disclosure (ED) influences tax avoidance, and how CG functions as a moderator for the impact of ED on tax avoidance. Between 2018 and 2021, we conducted 184 observations on 46 energy-related enterprises. The sample technique employed was purposive sampling. We used moderated regression analysis (MRA) regression with the random effects model to verify the hypothesis. According to the research conclusions, ED had no discernible impact on tax avoidance, CG had no bearing on it, and CG did not mitigate the impact of ED on tax avoidance. Tax avoidance is positively impacted by variable control size, MKTB, negatively impacted by ROA, and unaffected by leverage. Because environmental disclosure by energy corporations in Indonesia is still deficient despite being mandated, this research offers implications that could help regulators improve the quality of environmental disclosure Whether it is still in the meeting with the regulator stage or has already begun to improve governance, provide feedback to regulators so they can keep an eye on the CG implementation in Indonesia.